2017
DOI: 10.1101/152405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex polymorphisms in endocytosis genes suggest alpha-cyclodextrin as a treatment for breast cancer

Abstract: Most breast cancer deaths are caused by metastasis and treatment options beyond radiation and cytotoxic drugs, which have severe side effects, and hormonal treatments, which are or become ineffective for many patients, are urgently needed. This study reanalyzed existing data from three genome-wide association studies (GWAS) using a novel computational biostatistics approach (muGWAS), which had been validated in studies of 600-2000 subjects in epilepsy and autism. MuGWAS jointly analyzes several neighboring sin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 165 publications
(188 reference statements)
0
6
0
Order By: Relevance
“…FGF10-induced cell cycle progression depends on EGFR_T693 phosphorylation. COSMIC database (Tate et al, 2019) and the importance of trafficking proteins in breast cancer is emerging (Wittkowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FGF10-induced cell cycle progression depends on EGFR_T693 phosphorylation. COSMIC database (Tate et al, 2019) and the importance of trafficking proteins in breast cancer is emerging (Wittkowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting pan RTK trafficking (Porebska et␣al, 2018) and trafficking players, like TTP, RCP, and those identified by TPAs might open up novel therapeutic scenarios for treatment. Indeed, most of the recycling players identified here are mutated in breast cancer according to the COSMIC database (Tate et␣al, 2019) and the importance of trafficking proteins in breast cancer is emerging (Wittkowski et␣al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting pan RTK trafficking (Porebska et al, 2018) and trafficking players, like TTP, RCP, and those identified by TPAs might open up novel therapeutic scenarios for treatment. Indeed, most of the recycling players identified here are mutated in breast cancer according to the COSMIC database (Tate et al, 2019) and the importance of trafficking proteins in breast cancer is emerging (Wittkowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting pan RTK trafficking(Porebska et al, 2018) and trafficking players, like TTP, RCP, and those identified by TPAs might open up novel therapeutic scenarios for treatment. Indeed, most of the recycling players identified here are mutated in BC according to the COSMIC database(Tate et al, 2019) and the importance of trafficking proteins in BC is emerging(Wittkowski et al, 2018).Understanding the extent of RTK regulation "in the right place at the right time" (Barrow-McGee & Kermorgant, 2014) is key for the integration of early signaling and long-term responses in cancer cells. Here, we unveiled a new form of RTK communication, a reciprocal priming within the RE.…”
mentioning
confidence: 94%